Competitive Advantage As A Key Factor In Shaping The Economic Security of Enterprises - Waldemar Kunz; Adam Döring (Communications of International Proceedings, 2024)
The modern economy is characterized by high volatility, and doing business under the current conditions is becoming an increasingly difficult task. Under such conditions, the competitive advantage of enterprises is gaining new importance, as a key tool for creating economic security for enterprises, especially in the current turbulent post-pandemic times and in the face of the energy crisis. The area of research covered the issue of competitiveness of enterprises in the development sector, due to the fact that the construction sector is a large component of the national gross product, thereby having a significant impact on the national economy, including the labor market. It also has a major impact on the country's infrastructure, including, among other things, aesthetic and environmental issues, which translate directly into the quality of life of citizens. And thirdly, small and medium-sized developers, which are the subject of this paper, are not frequent objects of analysis, so there is a perceived deficiency and gap in knowledge on this subject, which the author will try to explore. The purpose of this article is to identify the key factors shaping the competitive advantage of real estate development enterprises as a tool for shaping economic security.  The research thesis is that the main source of competitive advantage of development sector enterprises is the intangible resources they possess.
Keywords: economy; security; motivation; enterprise; management engineering